Odpowiedzi

  • Roma
  • Community Manager
2010-02-27T19:33:24+01:00
Y= 2x-3
a = 2 b = - 3

y=-x+5
a = - 1 b = 5

y=-3x+4
a = - 3 b = 4

y=-7x
a = - 7 b = 0

y=-3
a = 0 b = - 3

y=0
a = 0 b = 0

y=-3-4x
a = - 4 b = - 3
1 5 1
2010-02-27T19:46:48+01:00
Y= 2x-3 (a =2 b = -3 )
y=-x+5 (a =-1 b =5)
y=-3x+4 (a=-3 b = 4)
y=-7x ( a = -7 b = 0 )
y=-3 (a= 0 b = -3 )
y=0 (a=0 b=0)
y=-3-4x ( a = -4 b = -3 )
1 1 1
2010-02-27T20:09:30+01:00
1)a=2 b=-3
2)a=-1 b=5
3)a=-3 b=4
4)a=-7 b=0
5)a=0 b=-3
6)a=0 b=0
7)a=-4 b=-3
1 2 1